Synthesis, complexation behavior and catalytic performance of chelating bisphosphite ligands based on 9,10-brigded 9,10-dihydroanthracenes in Rh catalyzed hydroformylation of 4-pentenal - Bondzic, Bojan; Rominger, Frank; Hofmann, Peter (Journal of molecular catalysis. A, Chemical, 2016)
In the present work the modular synthesis of new chelating bisphosphite ligands based on 9,10-brigded 9,10-dihydroanthracenes as ligand backbones is presented. The complexation behavior of these ligands in rhodium metal complexes as well as mechanistic studies of the preformation step of the rhodium-catalysed hydroformylation is investigated. Ratio of coordination isomers in the Rh complexes of these ligands has been determined using NMR based calculation technique. Modular synthesis route was established allowing for a variety of ligands to be synthesized in a standard procedure The new ligands were tested in the hydroformylation of 4-pentenal under optimized conditions to give adipic aldehyde a promising starting material for the polyamide nylon-6,6. Ligand L3 showed the best selectivity towards adipic aldehyde with selectivity of 10.2/1 n/iso aldehyde.